A Catalytic, One-pot and Green Synthesis of α-Amino Nitriles: Cu(BF4)2.x H2O an Efficient Catalyst - Tadiparthi, Krishnaji; Raghavendra, S.; Kamal, Ahmed (Letters in Organic Chemistry, 2017)
Background: The Strecker reaction is a first reported multicomponent reaction for the preparation of a-aminonitriles. The a-aminonitriles are important intermediates for various aminoacids, 1,2-diazines, heterocycles and biologically active compounds like Saframycin A and Ecteinascidin 746. The preparation of a-aminonitriles by Strecker approach using MCR attracted many research groups owing atom economy to avoid multistep synthesis and to follow Green chemistry principles. Methods: A-aminonitriles have been synthesized using Strecker reaction by treatment of aldehydes, amines, with TMSCN in the presence of Cu(BF4)2.xH2O as a catalyst in one pot under neat conditions. Various aromatic and aliphatic aldehydes have been studied with different primary and secondary amines. Results: The reaction condition has been optimized by choosing a model reaction under various solvents and found good yields under neat conditions. Moreover, various catalytic amounts of Cu(BF4)2.xH2O has also been studied and found 3 mole% providing better yields. The reaction has been studied with different substrates of aldehydes and amines. Some of the products were characterized by comparison of their spectral data (1H NMR, 13C NMR, IR and MS) and physical properties with those of authentic samples reported in the literature. Conclusion: Afacile and efficient one-pot synthesis of a-amino nitriles at ambient temperature using copper(II)tetrafluoroborate as a novel catalyst under solvent-free conditions via Strecker reaction is reported. The process is simple and environmentally benign using the commercially available and inexpensive catalyst.
Keywords: α-Amino nitriles